Neuromuscular differences between volleyball players, middle distance runners and untrained controls - Sleivert, G. G.; Backus, R. D.; Wenger, H. A. (International Journal of Sports Medicine, 1995)
Volleyball players, middle distance runners and non-athletes (n = 10/group) were tested to determine whether neuromuscular differences existed between groups and to clarify the roles of factors involved in maximal power production. The runners were leaner than controls, while the volleyball players were taller, heavier and had larger thigh volumes than the other groups. The volleyball players had higher absolute cycle ergometer power than both middle distance (26%) and control (15%) groups, but differences disappeared when expressed relative to body mass or thigh volume. Volleyball athletes were also stronger than both middle distance (51, 52%) and control subjects (33, 35%) for isokinetic leg extension and plantar flexion respectively (0-4.19 rad.s-1). In leg press they were stronger than middle distance (32%) and control subjects (36%) for only the isometric and 1.05 rad.s-1 contraction. The volleyball players also had higher rates of isometric torque development than the other groups, however nerve conduction velocity did not vary. Vastus lateralis biopsy samples revealed no differences in percent Type II muscle fibers, or fiber cross-sectional area between groups, yet volleyball athletes had larger Type II/I fiber area ratio than controls (15%). Both strength, rate of torque development and power were related to muscle and muscle fiber size variables, but not fiber distribution or nerve conduction velocity. The size of type II muscle fibers seemed to be especially important since this was the only variable related to power when adjusted for body size.